Catalytic Mechanisms and Design Principles for Single‐Atom Catalysts in Highly Efficient CO2 Conversion - Gong, Lele; Zhang, Detao; Lin, Chun‐Yu; Zhu, Yonghao; Shen, Yang; Zhang, Jing; Han, Xiao; Zhang, Lipeng; Xia, Zhenhai (Advanced energy materials, 2019)
Direct conversion of CO2 into carbon‐neutral fuels or industrial chemicals holds a great promise for renewable energy storage and mitigation of greenhouse gas emission. However, experimentally finding an electrocatalyst for specific final products with high efficiency and high selectivity poses serious challenges due to multiple electron transfer, complicated intermediates, and numerous reaction pathways in electrocatalytic CO2 reduction. Here, an intrinsic descriptor that correlates the catalytic activity with the topological, bonding, and electronic structures of catalytic centers on M–N–C based single‐atom catalysts is discovered. The “volcano”‐shaped relationships between the descriptor and catalytic activity are established from which the best single‐atom catalysts for CO2 reduction are found. Moreover, the reaction mechanisms, intermediates, reaction pathways, and final products can also be distinguished by this new descriptor. The descriptor can also be used to predict the activity of the single‐atom catalysts for electrochemical reactions such as hydrogen evolution, oxygen reduction and evolution reactions in fuel cells and water‐splitting. These predictions are confirmed by the experimental results for onset potential and Faraday efficiency. The design principles derived from the descriptors open a door for rational design and rapid screening of highly efficient electrocatalysts for CO2 conversion as well as other electrochemical energy systems. An intrinsic descriptor that correlates the catalytic activity with the topological, bonding, and electronic structures of catalytic centers on M–N–C based single‐atom catalysts is discovered. The “volcano”‐shaped relationships between the descriptor and catalytic activity are established from which the best single‐atom catalysts for CO2 reduction are found. The descriptor can also be used for other energy‐related electrochemical reactions.